Utilization of Inferiorly Based Dermofat Flap in Breast Reconstruction after Simple Mastectomy due to Gigantomastia - A. Bogdanov-Berezovsky; Y. Krieger; Y. Shoham; E. Silberstein (Case Reports in Surgery)
Gigantomastia (GM) is a rare disabling condition characterized by excessive breast tissue growth. To date, there is no universal classification and definition of GM. At present, GM is determined as weight over 1.5 kg per breast (Dancey et al., 2008) or 3% or more of the patient’s total body weight (Dafydd et al., 2011). The lack of generally acknowledged approach regarding GM is expressed by the different methods of its treatment ranging from hormonal prescription to mastectomy and subsequent complex breast reconstruction (Shoma et al., 2011). We describe a treatment approach, including simple mastectomy and immediate breast reconstruction by an inferiorly based dermofat flap with silicone implants and nipple grafting.